Caseinophosphopeptides released after tryptic hydrolysis versus simulated gastrointestinal digestion of a casein-derived by-product. (1st February 2015) - Cruz-Huerta, E.; García-Nebot, M.J.; Miralles, B.; Recio, I.; Amigo, L.
Highlights: Production of phosphopeptides from a casein by-product was achieved with trypsin. The precipitation pH and hydrolysis time can modulate the recovery of some sequences. Comparison with peptides released by simulated gastrointestinal digestion was done. Large homology was found between trypsin hydrolysis and simulated digestion products. The studied casein by-product can be exploited as a source of caseinophosphopeptides. Abstract: The production of caseinophosphopeptides from a casein-derived by-product generated during the manufacture of a functional ingredient based on antihypertensive peptides was attempted. The casein by-product was submitted to tryptic hydrolysis for 30, 60 and 120 min and further precipitated with calcium chloride and ethanol at pH 4.0, 6.0 and 8.0. Identification and semi quantification of the derived products by tandem mass spectrometry revealed some qualitative and quantitative changes in the released caseinophosphopeptides over time at the different precipitation pHs. The by-product was also subjected to simulated gastrointestinal digestion. Comparison of the resulting peptides showed large sequence homology in the phosphopeptides released by tryptic hydrolysis and simulated gastrointestinal digestion. Some regions, specifically αS1 -CN 43-59, αS1 -CN 60-74, β-CN 1-25 and β-CN 30-50 showed resistance to both tryptic hydrolysis and simulated digestion. The results of the present study suggest that this casein-derived by-product can be used as a source of CPPs.